1075. In vitro Activity of Gepotidacin against Escherichia coli Causing Urinary Tract Infections in the United States, Including Molecularly Characterized Fluoroquinolone Resistant Subsets. (4th December 2021) - Mendes, Rodrigo E; Doyle, Timothy B; Arends, S J Ryan; Butler, Deborah; Scangarella-Oman, Nicole; Streit, Jennifer M; Castanheira, Mariana; Castanheira, Mariana
Abstract: Background: Gepotidacin (GEP) is a novel bacterial type II topoisomerase inhibitor in Phase 3 clinical trials for the treatment of gonorrhea and uncomplicated urinary tract infections (UTI). This study characterized fluoroquinolone (FQ)-not susceptible (not S) E. coli causing UTI in U.S. patients and evaluated the in vitro activity of GEP and comparators against various drug resistance (R) subsets. Methods: 1, 035 E. coli collected from 38 U.S. sites were included as part of the GEP Global UTI Surveillance Program (2019). Isolates were tested for susceptibility by broth microdilution. E. coli with MICs ≥0.5 mg/L for ciprofloxacin (not S) and/or ≥1 mg/L for levofloxacin (not S) were selected for screening of FQ-R mechanisms, and subjected to genome sequencing, followed by screening of FQ-R genes and QRDR mutations in GyrA, GyrB, ParC and ParE. Results: A total of 26.8% (277/1, 035) E. coli met the screening criteria for FQ-not S (Table). Overall, GEP had MIC90 values of 2 mg/L and 4 mg/L against FQ-S and FQ-not S isolates, respectively. Nitrofurantoin had activity against the FQ-S and FQ-not S subsets (98.8% and 94.2%S, respectively), whereas amoxicillin-clavulanate (86.5% and 59.6%S) and trimethoprim-sulfamethoxazole (75.8% and 37.0%S) had limited activity. Most FQ-not S isolates (52.7%; 146/277) had double mutations in GyrA and ParC, followed by those isolates (20.6%; 57/277) with double mutations in GyrA and single mutations in ParC and ParE. The third most common genotype was represented by isolates (14.8%;41/277) with double mutations in GyrA and a single mutation in ParC. GEP had MIC50 values of 1 mg/L or 2 mg/L and MIC90 values of 2 mg/L or 4 mg/L when tested against isolates with various combinations of QRDR mutations. 4.3% (12/277) of FQ-not S E. coli carried qnrB (6) or qnrS (6), and GEP (MIC50/90, 8/16 mg/L) had MICs of 0.5–32 mg/L against this subset. Conclusion: GEP demonstrated potent activity against FQ-S and FQ-not S E. coli causing UTI in the U.S. In addition, GEP MIC did not seem to be affected by any combinations of FQ-R genes and QRDR mutations tested, except against the rare presence of qnrB/S genes. These data support the clinical development of GEP as a treatment option for UTI caused by FQ-S and FQ-not S E. coli isolates. Table Disclosures: Rodrigo E. Mendes, PhD, AbbVie (Research Grant or Support)AbbVie (formerly Allergan ) (Research Grant or Support)Cipla Therapeutics (Research Grant or Support)Cipla USA Inc. (Research Grant or Support)ContraFect Corporation (Research Grant or Support)GlaxoSmithKline, LLC (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support)Melinta Therapeutics, LLC (Research Grant or Support)Nabriva Therapeutics (Research Grant or Support)Pfizer, Inc. (Research Grant or Support)Shionogi (Research Grant or Support)Spero Therapeutics (Research Grant or Support) Timothy B. Doyle, AbbVie (formerly Allergan ) (Research Grant or Support)Bravos Biosciences (Research Grant or Support)GlaxoSmithKline (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support)Pfizer, Inc. (Research Grant or Support)Shionogi (Research Grant or Support)Spero Therapeutics (Research Grant or Support) S J Ryan Arends, PhD, AbbVie (formerly Allergan ) (Research Grant or Support)GlaxoSmithKline, LLC (Research Grant or Support)Melinta Therapeutics, LLC (Research Grant or Support)Nabriva Therapeutics (Research Grant or Support)Spero Therapeutics (Research Grant or Support) Deborah Butler, n/a, GlaxoSmithKline, LLC (Employee) Nicole Scangarella-Oman, MS, GlaxoSmithKline, LLC (Employee) Jennifer M. Streit, BS, GlaxoSmithKline, LLC (Research Grant or Support)Melinta Therapeutics, LLC (Research Grant or Support)Shionogi (Research Grant or Support)Spero Therapeutics (Research Grant or Support) Mariana Castanheira, PhD, AbbVie (formerly Allergan ) (Research Grant or Support)Bravos Biosciences (Research Grant or Support)Cidara Therapeutics, Inc. (Research Grant or Support)Cipla Therapeutics (Research Grant or Support)Cipla USA Inc. (Research Grant or Support)GlaxoSmithKline (Research Grant or Support)Melinta Therapeutics, Inc. (Research Grant or Support)Melinta Therapeutics, LLC (Research Grant or Support)Pfizer, Inc. (Research Grant or Support)Qpex Biopharma (Research Grant or Support)Shionogi (Research Grant or Support)Spero Therapeutics (Research Grant or Support) Mariana Castanheira, PhD, Affinity Biosensors (Individual(s) Involved: Self): Research Grant or Support; Allergan (Individual(s) Involved: Self): Research Grant or Support; Amicrobe, Inc (Individual(s) Involved: Self): Research Grant or Support; Amplyx Pharma (Individual(s) Involved: Self): Research Grant or Support; Artugen Therapeutics USA, Inc. (Individual(s) Involved: Self): Research Grant or Support; Astellas (Individual(s) Involved: Self): Research Grant or Support; Basilea (Individual(s) Involved: Self): Research Grant or Support; Beth Israel Deaconess Medical Center (Individual(s) Involved: Self): Research Grant or Support; BIDMC (Individual(s) Involved: Self): Research Grant or Support; bioMerieux Inc. (Individual(s) Involved: Self): Research Grant or Support; BioVersys Ag (Individual(s) Involved: Self): Research Grant or Support; Bugworks (Individual(s) Involved: Self): Research Grant or Support; Cidara (Individual(s) Involved: Self): Research Grant or Support; Cipla (Individual(s) Involved: Self): Research Grant or Support; Contrafect (Individual(s) Involved: Self): Research Grant or Support; Cormedix (Individual(s) Involved: Self): Research Grant or Support; Crestone, Inc. (Individual(s) Involved: Self): Research Grant or Support; Curza (Individual(s) Involved: Self): Research Grant or Support; CXC7 (Individual(s) Involved: Self): Research Grant or Support; Entasis (Individual(s) Involved: Self): Research Grant or Support; Fedora Pharmaceutical (Individual(s) Involved: Self): Research Grant or Support; Fimbrion Therapeutics (Individual(s) Involved: Self): Research Grant or Support; Fox Chase (Individual(s) Involved: Self): Research Grant or Support; GlaxoSmithKline (Individual(s) Involved: Self): Research Grant or Support; Guardian Therapeutics (Individual(s) Involved: Self): Research Grant or Support; Hardy Diagnostics (Individual(s) Involved: Self): Research Grant or Support; IHMA (Individual(s) Involved: Self): Research Grant or Support; Janssen Research & Development (Individual(s) Involved: Self): Research Grant or Support; Johnson & Johnson (Individual(s) Involved: Self): Research Grant or Support; Kaleido Biosceinces (Individual(s) Involved: Self): Research Grant or Support; KBP Biosciences (Individual(s) Involved: Self): Research Grant or Support; Luminex (Individual(s) Involved: Self): Research Grant or Support; Matrivax (Individual(s) Involved: Self): Research Grant or Support; Mayo Clinic (Individual(s) Involved: Self): Research Grant or Support; Medpace (Individual(s) Involved: Self): Research Grant or Support; Meiji Seika Pharma Co., Ltd. (Individual(s) Involved: Self): Research Grant or Support; Melinta (Individual(s) Involved: Self): Research Grant or Support; Menarini (Individual(s) Involved: Self): Research Grant or Support; Merck (Individual(s) Involved: Self): Research Grant or Support; Meridian Bioscience Inc. (Individual(s) Involved: Self): Research Grant or Support; Micromyx (Individual(s) Involved: Self): Research Grant or Support; MicuRx (Individual(s) Involved: Self): Research Grant or Support; N8 Medical (Individual(s) Involved: Self): Research Grant or Support; Nabriva (Individual(s) Involved: Self): Research Grant or Support; National Institutes of Health (Individual(s) Involved: Self): Research Grant or Support; National University of Singapore (Individual(s) Involved: Self): Research Grant or Support; North Bristol NHS Trust (Individual(s) Involved: Self): Research Grant or Support; Novome Biotechnologies (Individual(s) Involved: Self): Research Grant or Support; Paratek (Individual(s) Involved: Self): Research Grant or Support; Pfizer (Individual(s) Involved: Self): Research Grant or Support; Prokaryotics Inc. (Individual(s) Involved: Self): Research Grant or Support; QPEX Biopharma (Individual(s) Involved: Self): Research Grant or Support; Rhode Island Hospital (Individual(s) Involved: Self): Research Grant or Support; RIHML (Individual(s) Involved: Self): Research Grant or Support; Roche (Individual(s) Involved: Self): Research Grant or Support; Roivant (Individual(s) Involved: Self): Research Grant or Support; Salvat (Individual(s) Involved: Self): Research Grant or Support; Scynexis (Individual(s) Involved: Self): Research Grant or Support; SeLux Diagnostics (Individual(s) Involved: Self): Research Grant or Support; Shionogi (Individual(s) Involved: Self): Research Grant or Support; Specific Diagnostics (Individual(s) Involved: Self): Research Grant or Support; Spero (Individual(s) Involved: Self): Research Grant or Support; SuperTrans Medical LT (Individual(s) Involved: Self): Research Grant or Support; T2 Biosystems (Individual(s) Involved: Self): Research Grant or Support; The University of Queensland (Individual(s) Involved: Self): Research Grant or Support; Thermo Fisher Scientific (Individual(s) Involved: Self): Research Grant or Support; Tufts Medical Center (Individual(s) Involved: Self): Research Grant or Support; Universite de Sherbrooke (Individual(s) Involved: Self): Research Grant or Support; University of Iowa (Individual(s) Involved: Self): Research Grant or Support; University of Iowa Hospitals and Clinics (Individual(s) Involved: Self): Research Grant or Support; University of Wisconsin (Individual(s) Involved: Self): Research Grant or Support; UNT System College of Pharmacy (Individual(s) Involved: Self): Research Grant or Support; URMC (Individual(s) Involved: Self): Research Grant or Support; UT Southwestern (Individual(s) Involved: Self): Research Grant or Support; VenatoRx (Individual(s) Involved: Self): Research Grant or Support; Viosera Therapeutics (Individual(s) Involved: Self): Research Grant or Support; Wayne State University (Individual(s) Involved: Self): Research Grant or Support